ANALISIS TENTANG KENDALA-KENDALA YANG DIHADAPI ORANG TUA DALAM PEMBINAAN AKHLAK DAN KEDISIPLINAN BELAJAR SISWA MADRASAH DARUSSALAM KOTA BENGKULU - Irhamna Irhamna (UIN Fatmawati Sukarno Bengkulu, 2016)
In the moral development of children, parents still get a lot of obstacles, in addition to the educational level of parents is low and parents are also not yet fully understand the task in coaching children good morals by religion and the discipline of learning. This analysis technique using the deductive method that is how that is done with the express thoughts or opinions to get a sense of the prevailing opinion is then taken into the opinion that special sense. Based on the research results, it can be concluded that: First, constraints faced by elderly people that a lack of time with the child as a result of busy work outside the home, lack of knowledge to educate children about religion, association of children in the neighborhood and the understanding and awareness of the child is not maximized. Second, the constraints faced by parents in giving discipline of learning in children due to busy work outside, their influence in a child's environment as well hang a huge lack of awareness of children themselves in the discipline. Third, the effectiveness of moral guidance and discipline of children's learning in general it can be said still need guidance, especially depraved state.